Facile, Mild-Temperature Synthesis of Metal-Free Phthalocyanines - Cong, Fangdi; Jiang, Hongzhen; Du, Xiguang; Yang, Wei; Zhang, Shulin (Synthesis, 2021)
It is important for the synthesis and research of phthalocyanine compounds for these compounds to be easily obtained at low temperature. We observed that metal-free phthalocyanine was sometimes found in a simple system used to synthesize phthalocyanine precursors at room temperature, and further studies showed that the key to the effective formation of phthalocyanines at low temperature lay in the presence of equal volumes of alcohol and amine, in addition to substrate phthalonitriles and solvents, in the reaction system. A synthetic mechanism was proposed and facile syntheses have been realized, such as the synthesis of tetra-α(β)-nitrophthalocyanines and tetra-α(β)-(4-tert-butylphenoxy)phthalocyanines from the corresponding substituted phthalonitriles at mild temperature (37 °C). The results are significant for the design and synthesis of new phthalocyanine derivatives, and the method is convenient and easy to adopt for general use in standard laboratories.
Keywords: metal-free phthalocyanine; facile synthesis; characterization; room temperature; amine; alcohol; phthalonitrile